CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND LEVERAGE ON COMPANY FINANCIAL PERFORMANCE - Mahdy, Keane Aldyth; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2025)
This research is conducted to find empirical evidence on the disclosure of social responsibility activities (CSRD) and the use of leverage level (DER) set by the company on the financial performance (ROA) of the company concerned. This study will involve 45 companies as research samples. The use of 45 companies as research samples is obtained from a total population of 84 companies that have met the criteria in the study. The 45 sample companies are companies engaged in the energy sector and have been listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. In this study, SPSS 23 is software that is a tool for researchers to test the processing of each data used in the study. Multiple regression analysis is the analysis method used in this study. In this study, it was found that H1 was rejected and H2 was accepted. Based on these results, it can be concluded that the disclosure of corporate social responsibility (CSRD) has no influence on the financial performance (ROA) of the company concerned, while leverage (DER) has an influence on the financial performance of the company concerned. However, simultaneously the disclosure of corporate social responsibility (CSRD) and leverage (DER) has an influence on financial performance (ROA). The results will provide consideration to stakeholders in selecting energy sector companies to make investment decisions.